Model for Calculating Seismic Wave Spectrum Excited by Explosive Source - Qian Xu; Zhong-Qi Wang (Shock and Vibration)
To reveal the characteristics and laws of the seismic wavefield amplitude-frequency excited by explosive source, the method for computing the seismic wave spectrum excited by explosive was studied in this paper. The model for calculating the seismic wave spectrum excited by explosive source was acquired by taking the seismic source model of spherical cavity as the basis. The results of using this model show that the main frequency and the bandwidth of the seismic waves caused by the explosion are influenced by the initial detonation pressure, the adiabatic expansion of the explosive, and the geotechnical parameters, which increase with the reduction of initial detonation pressure and the increase of the adiabatic expansion. The main frequency and the bandwidth of the seismic waves formed by the detonation of the explosives in the silt clay increase by 23.2% and 13.6% compared to those exploded in the silt. The research shows that the theoretical model built up in this study can describe the characteristics of the seismic wave spectrum excited by explosive in a comparatively accurate way.